The challenges and conservation implications of bear bile farming in Viet Nam. Issue 2 (2nd March 2020) - Crudge, Brian; Nguyen, Trang; Cao, Tien Trung
Abstract: Legalized trade in commercially farmed wildlife products is sometimes promoted as a conservation strategy. In theory, flooding the market with cheaper or better quality products will decrease the profitability of poaching. Bear bile is highly sought-after for use in traditional medicine and overhunting to supply the demand for bear parts has led to declining populations across South-east Asia. Bear bile farming was established to help supply the high demand for bear bile. In Viet Nam it is legal to keep registered bears, but illegal to extract or sell bear bile. We conducted semi-structured interviews with 66 bear bile farmers in Viet Nam to examine the conservation implications of bear bile farming. The results show that demand for wild bear bile was not satisfied by the widespread availability of farmed bear bile. Farmers report a strong consumer preference and willingness to pay more for wild-sourced products. The existence of bear bile farms presents considerable challenges to law enforcement. The results suggest that bear bile farming in Viet Nam relies on restocking from wild populations, and farmers openly admit to extracting and selling bear bile, in clear violation of national legislation. The case of bear bile farming in Viet Nam provides an example of wildlife farming failing to reduce pressure on a once widely distributed and relatively abundant species. Research into consumer values, attitudes and behaviours will help to improve understanding of market drivers and help inform the design of effective species conservation and management strategies.